Análisis de cepas diarreogénicas de Escherichia coli provenientes de bovinos de Tierra del Fuego y su posible impacto en la salud - Bonino, María Paz (2020)
Shiga toxin producing E. coli (STEC), which has endemic presentation in Argentina,\nand enteropathogenic E. coli (EPEC), are probably the most significant pathovars, known for causing disease in childhood health. STEC pathogenesis includes mild to severe diarrhea,\nhemolytic uremic syndrome (HUS) which can lead to death. Cattle have been recognized as\nthe main reservoir of STEC. EPEC causes diarrhea and have been reported to be the second cause of death in under five-year-old children. In Tierra del Fuego (TDF), SUH and diarrheas\nhave high rates. There are no previous studies of carriers or reservoirs of STEC and EPEC in\nTDF. The aim of this study was to establish the prevalence of STEC and EPEC in cattle from\nslaughterhouses in TDF. A cross-sectional epidemiological study was carried out in July 2016\nto determine the prevalence of STEC, EPEC and AE-STEC in cattle being raised for consumption in TDF. Samples were taken in two slaughterhouses in TDF (Ushuaia y Río Grande). We collected one rectal swab from each animal. For non-O157 STEC and EPEC\neach sample was enriched in tryptone soy broth. Later, the samples were cultivated on MacConckey agar. For O157 STEC inmunomagnetic separation was carried out. Screening\nwas carried out using conventional PCR for stx1, stx2, rfbO157 and eae genes. Positive\nsamples at screening were analysed looking for positive pathovar strains. Each isolated strain was biochemically characterized and serotyped. Subtyping of stx1 and stx2 were performed by PCR, and Shigatoxin and enterohemolysin production were carried out in STEC strains.The presence of the bfpA gene, and strain adhesion pattern was determined in isolated EPEC\nstrains. Antimicrobial susceptibility was test for each isolate. Statistical analysis was carried\nout using Test of Differences. A total of 194 samples were analysed. The prevalence of STEC\nwas 15% (30/194), and the prevalence of EPEC was 5% (10/194). Twenty eight strains were isolated. STEC strains had the following serotypes: O1:H21 (1/27); O6:H34 (1/27); O113:H21\n(1/27); O130:H11 (1/27); O130:H- (1/27); O171:H2 (1/27); O174:H28 (1/27); O178:H19 (5/27);\nO179:H8 (1/27); O185:H7 (6/27); O185:H19 (7/27); O187:H7 (1/27) and EPEC strain belong to O152:H25 serogroup. AE-STEC nor serogroup O157 were not detected in this study. The\nmain toxin type in STEC strains was stx2 (92,6%). The stx types detected were stx2 (16/27), stx1/stx2 (9/27) and stx1 (2/27). The most prevalent stx genotypes was stx2c (37%). 14% of\nthe strains showed at least one nontypeable subtype (4/27). Shiga toxin production was\ndetected in 25/27 STEC strains. EPEC strain was categorized as atypical with no specific adhesion pattern and with the ability to cause A/E lesion. The ehxA gene was present in 16/28\nstrains, 12 of them produced enterohemolisin. There were no hybrid strains detected in this work. Antimicrobial susceptibility tests showed that all the strains were resistant to ampicillin,\nand 20/28 were resistant to aminoglycosides (20/20 streptomycin with 6/20 amikacin). No significant difference could be seen in the detection of STEC or EPEC by slaughterhouse or \nXIV production (extensive or intensive). EPEC/STEC relation was 1/3, which means that it´s three\ntimes more likely to be infected by STEC tan by EPEC and there is no cross reactive immunity between strains